Engaging With Contemporary Dance: What Can Body Movements Tell us About Audience Responses? - Theodorou, Lida; Healey, Patrick G. T.; Smeraldi, Fabrizio (Frontiers in Psychology, 2019)
3 In live performances seated audiences have restricted opportunities for response. Some 4 responses are obvious, such as applause and cheering, but there are also many apparently 5 incidental movements including posture shifts, fixing hair, scratching and adjusting glasses. 6 Do these movements provide clues to people’s level of engagement with a performance? Our 7 basic hypothesis is that audience responses are part of a bi-directional system of audience- 8 performer communication. This communication is part of what distinguishes live from recorded 9 performance and underpins live performers’ moment-to-moment sense of how well a performance 10 is going. Here we investigate the range of visible real-time movements of audiences in four live 11 contemporary dance performances. Video recordings of performers and audiences were analysed 12 using computer vision techniques for extracting face, hand and body movement data. The 13 meaning of audience movements were analysed by comparing clips of the audience at moments 14 of maximum and minimum movement to expert and novice judges. The results show that audience 15 clips with the lowest overall movement are judged as displaying the highest engagement. In 16 addition, we found that while there is no systematic relationship between audience and dancers 17 movement, hands seem to play an especially significant role since they move significantly more 18 compared to the rest of the body. We draw on these findings to argue that collective stillness is 19 an especially salient signal of audience engagement.